Potential Biological Roles of Exosomal Long Non-Coding RNAs in Gastrointestinal Cancer - Kang, Fanhua; Jiang, Feng; Ouyang, Lingzi; Wu, Shangjun; Fu, Chencheng; Liu, Ying; Li, Zhilan; Tian, Yu; Cao, Xiaolan; Wang, Xiaoping; He, Qingchun (Frontiers in Cell and Developmental Biology, 2022)
Exosomes, a type of extracellular vesicles (EVs), are secreted by almost all cells and contain many cellular constituents, such as nucleic acids, lipids, and metabolites. In addition, they play a crucial role in intercellular communication and have been proved to be involved in the development and treatment of gastrointestinal cancer. It has been confirmed that long non-coding RNAs (lncRNAs) exert a range of biological functions, such as cell metastasis, tumorigenesis, and therapeutic responses. This review mainly focused on the emerging roles and underlying molecular mechanisms of exosome-derived lncRNAs in gastrointestinal cancer in recent years. The biological roles of exosomal lncRNAs in the pathogenesis and therapeutic responses of gastrointestinal cancers were also investigated.